2022
DOI: 10.2147/jhc.s344559
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Due to Nonalcoholic Fatty Liver Disease: Current Concepts and Future Challenges

Abstract: Obesity has been labeled as the global pandemic of the 21st century, resulting from a sedentary lifestyle and caloric excess. Nonalcoholic fatty liver disease (NAFLD), characterized by excessive hepatic steatosis, is strongly associated with obesity and metabolic syndrome and is estimated to be present in one-quarter of the world population, making it the most common cause of the chronic liver disease (CLD). NAFLD spectrum varies from simple steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 189 publications
1
19
0
Order By: Relevance
“…Because of the epidemic of obesity and T2DM, NAFLD is now the most frequent chronic liver disease worldwide with a global prevalence of 25% [ 32 ]. NAFLD comprises a large spectrum of histologic changes including simple fatty liver, nonalcoholic steatohepatitis (NASH), advanced fibrosis and cirrhosis [ 33 ], which can evolve into hepatocellular carcinoma (HCC) [ 34 ]. It is estimated that simple fatty liver progresses to NASH in about 10 to 20% of the patients [ 35 ].…”
Section: Apap Hepatotoxicity In Nafldmentioning
confidence: 99%
“…Because of the epidemic of obesity and T2DM, NAFLD is now the most frequent chronic liver disease worldwide with a global prevalence of 25% [ 32 ]. NAFLD comprises a large spectrum of histologic changes including simple fatty liver, nonalcoholic steatohepatitis (NASH), advanced fibrosis and cirrhosis [ 33 ], which can evolve into hepatocellular carcinoma (HCC) [ 34 ]. It is estimated that simple fatty liver progresses to NASH in about 10 to 20% of the patients [ 35 ].…”
Section: Apap Hepatotoxicity In Nafldmentioning
confidence: 99%
“…A subsequent meta-analytic study published by Thomas et al [19] by comparing 64 studies for analysis of incident HCC (625,984 patients) and extrahepatic cancer (41,027), found that extra-hepatic cancers were over 8-fold more common than HCC in NAFLD and were not associated with the stage of advanced hepatic fibrosis or cirrhosis. This is in striking contrast with HCC where the most advanced stages of liver fibrosis are associated with an increasing risk of disease [20,21]. Finally, an umbrella meta-analysis by Yi et al [22] based on the scrutiny of 39 published meta-analyses results found that individuals with NAFLD exhibited an increased risk of the following extra-hepatic cancers: thyroid, extra-hepatic and intra-hepatic cholangiocarcinoma, pancreatic, esophago-gastric, urinary tract, breast, and lung.…”
Section: Methods Findings Conclusionmentioning
confidence: 94%
“…Unlike HBV, the HCV protein modulates a wide range of cellular activities in HCV-induced HCC, including transcriptional regulation, epigenetic alterations, and cytokine modulation, all of which contribute to chronic liver injury, cirrhosis, and HCC development [6]. The pathological state characterized by insulin resistance, hyperglycemia, and inflammation in obesity and diabetes leads to increased endoplasmic reticulum (ER) stress and oxidative stress, changes in the gut microbiota, and dysregulated adipokines, all of which contribute to the pathogenesis of HCC [7]. Furthermore, the contribution of alcohol to the HCC burden varies across countries (Europe: 16-78%, America: 17-52%, Oceania: 15-37%, and lowest in Asia: 0-41%) [8].…”
Section: Introductionmentioning
confidence: 99%